Konsep Negara Sejahtera menurut Ibnu Taimiyah dan Relevansinya dengan Nilai Pancasila (Studi pada Masyarakat dan Pemerintahan Provinsi Aceh) - Miftah Pahlevi; Muhammad Azrul Amirullah (AHKAM, 2025)
The development of the Indonesian nation requires the integration of religious values and state ideology. Ibn Taymiyyah emphasized that a prosperous state must be built upon the principles of justice, trustworthy leadership, and adherence to Islamic law—concepts that resonate with Pancasila, particularly the fourth principle of democracy and the fifth principle of social justice. Aceh, as a region implementing Islamic law, provides an appropriate locus for examining the interconnection between classical Islamic thought and Indonesia’s modern ideology. This study aims to analyze Ibn Taymiyyah’s concept of a prosperous state and its relevance to Pancasila through a case study of the society and government of Aceh Province. A qualitative descriptive approach was applied using interviews, observations, and documentation conducted between May 14 and July 29, 2025. The findings demonstrate alignment between Ibn Taymiyyah’s ideas and Pancasila values, as reflected in the Aceh government’s efforts to balance the implementation of Islamic law with national principles. The people of Aceh also perceive prosperity as not only dependent on religious norms but also on economic justice and trustworthy leadership. The study concludes that Ibn Taymiyyah’s concept of a prosperous state and Pancasila values can complement one another in building a just and prosperous society grounded in both spiritual and national ideals.